(untitled) (Heritage, 2020)
Ljubiša Jocić, a companion of Serbian Surrealism, poet, novelist, narrator, essayist, actor, director, playwrighter, painter, left an insufficiently researched and extensive artistic legacy. In his overall artistic engagement, there is a noticeable motive unity, which is evident through the phenomena of the riddle of Eros, analysis and re-examination of the world and self, fear of evil in all its manifestations, to the search for harmony and original innocence of the world,. precisely in the space of the creative. In primary ideas, as well as in the procedures of building a literary text, Ljubiša Jocić was always outside the dominant poetics and generally accepted, suitable and canonized literary paradigms.